"Everything Is in the Lab Book": Multimodal Writing, Activity, and Genre Analysis of Symbolic Mediation in Medical Physics. (January 2022) - Doody, Sara; Artemeva, Natasha
Writing and genre scholarship has become increasingly attuned to how various nontextual features of written genres contribute to the kinds of social actions that the genres perform and to the activities that they mediate. Even though scholars have proposed different ways to account for nontextual features of genres, such attempts often remain undertheorized. By bringing together Writing, Activity, and Genre Research, and Multimodal Interaction Analysis, the authors propose a conceptual framework for multimodal activity-based analysis of genres, or Multimodal Writing, Activity, and Genre (MWAG) analysis. Furthermore, by drawing on previous studies of the laboratory notebook (lab book) genre, the article discusses the rhetorical action the genre performs and its role in mediating knowledge construction activities in science. The authors provide an illustrative example of the MWAG analysis of an emergent scientist's lab book and discuss its contributions to his increasing participation in medical physics. The study contributes to the development of a theoretically informed analytical framework for integrative multimodal and rhetorical genre analysis, while illustrating how the proposed framework can lead to the insights into the sociorhetorical roles multimodal genres play in mediating such activities as knowledge construction and disciplinary enculturation.